The application of whole-exome sequencing in the early diagnosis of rare genetic diseases in children: a study from Southeastern China - Lai, Guihua; Gu, Qiying; Lai, Zhiyong; Chen, Haijun; Chen, Junkun; Huang, Jungao (Frontiers in Pediatrics, 2024)
Background: Genetic diseases exhibit significant clinical and genetic diversity, leading to a complex and challenging diagnostic process. Exploiting novel approaches is imperative for the molecular diagnosis of genetic diseases. In this study, we utilized whole-exome sequencing (WES) to facilitate early diagnosis in patients suspected of genetic disorders.Methods: This retrospective analysis included 144 patients diagnosed by singleton-WES Trio-WES between January 2021 and December 2023. We investigated the relevance of diagnosis rates with age, clinical presentation, and sample type.Results: Among the 144 patients, 61 were diagnosed, yielding an overall diagnostic rate of 42.36%, with Trio-WES demonstrating a significantly higher diagnostic rate of 51.43% (36/70) compared to singleton-WES at 33.78% (25/74) (p < 0.05). Global developmental delay had a diagnosis rate of 67.39%, significantly higher than muscular hypotonia at 30.43% (p < 0.01) among different clinical phenotypic groups.Autosomal dominant disorders accounted for 70.49% (43/61) of positive cases, with autosomal abnormalities being fivefold more prevalent than sex chromosome abnormalities. Notably, sex chromosome abnormalities were more prevalent in males (80%, 8/10). Furthermore, 80.56% (29/36) of pathogenic variants were identified as de novo mutations through Trio-WES.Conclusions: These findings highlight the effectiveness of WES in identifying genetic variants, and elucidating the molecular basis of genetic diseases, ultimately enabling early diagnosis in affected children.